Tacitus and the Tacitean Tradition. - Luce, Torrey James (Princeton legacy library., 2014)
In this volume distinguished scholars from both sides of the Atlantic explore the work of Tacitus in its historical and literary context and also show how his text was interpreted in the sixteenth through eighteenth centuries. Discussed here, for example, are the ways predilections of a particular age color one's reading of a complex author and why a reexamination of these influences is necessary to understand both the author and those who have interpreted him. All of the essays were first prepared for a colloquium on Tacitus held at Princeton University in March 1990. The resulting volume.